The Relationship between Motivation Factors and Unsafe Action on Passenger Ship Crews in Tanjung Pinang - Jhonni Wahyudi; Gerry Silaban; Destanul Aulia (Britain International for Academic Research (BIAR) Publisher, 2020)
This research deals with the relationship between motivation factors and unsafe action on passenger ship crews in Tanjung Pinang. This type of research is an analytical survey using cross sectional design aimed at explaining a situation by analyzing the relationship between individual factors and work factors with unsafe action on the crew of passenger ships in Tanjung Pinang City. The study was conducted at the port of Sri Bintan Pura in Tanjung Pinang City. The population in this study is the crew of passenger ships with the position of Captain, Mualim, KKM (Head of Engine Room), and Oiler in the port of Sri Bintan Pura Tanjungpinang City with the destination of Tanjungpinang to Batam. Based on the results of the study indicate that there is a significant relationship between motivation and unsafe action. In the multivariate test, it is known that motivation variable has an influence on unsafe action with p value = 0.019 and exp (B) value of 8.577, which means that the motivation variable in the low category will cause unsafe action to be high by 8.577 times compared to the high motivation category. It can be conclude that the majority of respondents classified as young, have a high level of education, a new tenure, have a high income, good knowledge of occupational health and safety, high motivation, and unsafe action. Based on the bivariate analysis obtained levels of education, years of service, knowledge, motivation, related to unsafe action.